Novel solar-driven low temperature district heating and cooling system based on distributed half-effect absorption heat pumps with lithium bromide. (1st May 2023) - Sun, Fangtian; Zhao, Xiaoqing; Hao, Baoru
Abstract: Utilizing solar energy for space heating and cooling would contribute to achieving the goal of China's carbon emission peak by 2030. However, solar energy is featured by low energy density and intermittent energy output, and it mismatches with the continuous demand of high energy density in the Chinese Northern cities. For the solar-driven district heating and cooling system, both time and space mismatches between supply and demand are two key problems to be solved. To solve the two problems, a novel solar-driven low temperature district heating and cooling system based on distributed half-effect absorption heat pumps with lithium bromide is proposed, and it is analyzed by using thermodynamics and economics. Results show that the proposed novel solar-driven low temperature district heating and cooling system can achieve annual system coefficient of performance about 8.52, annual system product exergy efficiency about 36.7%, and cost-effectively heat transmission distance about 24.5 km. Compared with the conventional heating and cooling systems, the proposed novel solar-driven low temperature district heating and cooling system can reduce heating cost, cooling cost and annual carbon emission by about 27.14 ¥/GJ, 12.12 ¥/GJ and 23 kg per floor area, and it energy conversion and transfer process is advanced. Highlights: Half-effect absorption heat pump is suitable to improve new proposed energy system. Centralized and distributed thermal storage can solve solar energy time mismatch. New proposed energy system can improve ASCOP by about 8.52 and ASPEE by about 36.7%. New energy system can reduce heating and cooling costs by about 27 ¥/GJ and 12 ¥/GJ. New proposed energy system has an advanced energy conversion and transfer process.